2021
DOI: 10.3390/ijms221910808
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential and Main Methods of Obtaining Selenium Nanoparticles

Abstract: This review presents the latest data on the importance of selenium nanoparticles in human health, their use in medicine, and the main known methods of their production by various methods. In recent years, a multifaceted study of nanoscale complexes in medicine, including selenium nanoparticles, has become very important in view of a number of positive features that make it possible to create new drugs based on them or significantly improve the properties of existing drugs. It is known that selenium is an essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 204 publications
(230 reference statements)
1
48
0
Order By: Relevance
“…In control cell cultures of the mouse cerebral cortex, 8 ± 3% of necrotic cells can be recorded in vitro by Day 10 ( Figure 5 E,F), but after 40 min of OGD, necrosis is recorded in 83 ± 11% of cells. It is known that SeNPs have pleiotropic effects [ 23 ] and, on the one hand, activate apoptotic processes in cancer cells [ 17 , 24 ], but on the other hand, they are capable of exerting neuroprotective effects [ 25 ]. In addition, we have shown that the protective effects of the anti-inflammatory cytokine, interleukin-10, and antioxidants increase in proportion to the incubation time and are largely realized through the protection of astrocytes [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In control cell cultures of the mouse cerebral cortex, 8 ± 3% of necrotic cells can be recorded in vitro by Day 10 ( Figure 5 E,F), but after 40 min of OGD, necrosis is recorded in 83 ± 11% of cells. It is known that SeNPs have pleiotropic effects [ 23 ] and, on the one hand, activate apoptotic processes in cancer cells [ 17 , 24 ], but on the other hand, they are capable of exerting neuroprotective effects [ 25 ]. In addition, we have shown that the protective effects of the anti-inflammatory cytokine, interleukin-10, and antioxidants increase in proportion to the incubation time and are largely realized through the protection of astrocytes [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since Se has pronounced therapeutic potential for the treatment of viral infections and other conditions such as cancer, Se nanomedicine has received a lot of attention. Se nanoparticles are known to have low toxicity with marked and selective cytotoxic effects with small quantities [ 174 ]. Additionally, Se nanoparticles have high effectiveness in the inhibition of oxidative damage [ 175 , 176 , 177 ].…”
Section: Viral Infections and Seleniummentioning
confidence: 99%
“…Recently published data show that Se nanoparticles activate programmed cell death in target cancer tissue through calcium (Ca) 2+ signaling pathways [ 178 ]. Immune cells also require calcium flux to generate oxidative stress [ 174 ]. Through chemical methods, Se nanoparticles may be produced with Se sources that include sodium selenite, selenious acid, and sodium selenosulfate [ 174 ].…”
Section: Viral Infections and Seleniummentioning
confidence: 99%
See 1 more Smart Citation
“…SeNPs are able to cross the blood–brain barrier, accumulate in the brain and prevent the development of apoptosis in cells 18 – 21 . The uniqueness of nanoparticles is mediated by their properties—small size, high surface area, surface charge, surface chemistry, solubility and multi-functionality 22 , 23 . Nanoparticles are ideal for biomedical use because they are small enough (10–100 nm) not to be absorbed by the reticuloendothelial system, but large enough not to be filtered out in the kidneys 24 26 .…”
Section: Introductionmentioning
confidence: 99%